Genetic Diversity of I. tinctoria L. as Natural Batik Dye Based on Morphological Characters - Muzayyinah, Muzayyinah; Ramli, Murni; Nurmiyati, Nurmiyati (Universitas Sebelas Maret, 2015)
Indigofera tinctoria is one of the most important species frequently used to produce natural blue dye commercially. The leafy twigs are the main sourches of indigo dye use since very ancient time for dyeing textile blue. The source of blue colour is indigo, derived from indican. Some communities had been used as a dye since 352-395 AD in Indonesia. The aims of this research were: to analyzed morphological characters of Indigofera and studied the relationships among Indigofera species based on morphological data. Forty-nine samples of I. tinctoria L. were collected from 37 locations in Java and Madura islands. The results revealed that the characters length of petiole, the color of dried foliage upper surface, the color of dried foliage lower surface, crown shape, vexilum shape, indumentum bract, anther trichome, elevation and soil pH can group four accession. The similarity value among accessions was 50% and divided I. Tinctoriaaccessions into four groups in accordance with the sampling sites.Keyword: blue dye, diversity, indigo, indicant, Indigofera, morphological characters